Republic of Serbia : Second Review Under the Policy Coordination Instrument and Request for Modification of Targets-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2022)
The economy has navigated the COVID-19 pandemic well. In 2021, real GDP growth strongly rebounded by 7.4 percent, supporting a narrower fiscal deficit of 4.1 percent of GDP and a decline in the public debt ratio, and consistent with a return to pre-pandemic medium-term trend growth.